Avaliação da qualidade da água superficial em uma microbacia periurbana do município de Santarém - PA - BATISTA, Louisiane Farias (Universidade Federal do Oeste do Pará, 2024)
Surface waters are almost rarely free of pollution and contamination, even with little anthropic interaction. They are more susceptible environments, due to their very condition. The disorderly occupation around watercourses generates significant negative impacts on aquatic ecosystems. In this assumption, the present study aims to evaluate the water quality of the Juá watershed, located in peri-urban areas of the municipality of Santarém in western Pará. Six sampling points were selected and divided along the watershed, considering the main course and its tributaries. The sampling campaigns were carried out in different periods of the year, in the rainy season (February/2020 and January/2021) and in the less rainy season (November/2020 and September/2021), making it possible to visualize the influence of seasonal variations on the quality of the water body. The Water Quality Index - WQI developed by CETESB was calculated and compared to the standards established by CONAMA Resolution 357/2005 for class II waters. The application of the WQI showed that most of the monitored points are classified as REGULAR, however, it is worth pointing out that samples P4 and P5 behaved as BAD. When comparing the seasonality of the stations it is observed that the driest period showed the best indexes, this is explained by the fact that there is a greater carriage of pollutants into the bodies of water during the rainiest period. Compared to the CONAMA 357/2005, some values of dissolved oxygen (DO), pH, phosphorus (P), turbidity, and thermotolerant coliforms are not in compliance with the legislation, with concentrations 60 times higher than allowed, in the case of coliforms. The acid pH is considered natural in the region, due to the aquatic-forest interaction that results from the presence of humic and fulvic substances resulting from the decomposition of organic matter in the riparian forest. Furthermore, CONAMA 357/2005, as well as the WQI, does not consider the natural differences in the ecological processes of the Amazonian aquatic ecosystem, which is different from the other regions of the country. Therefore, it is evident the need to monitor the Amazonian urban micro-watersheds, which suffer from a rapid decline in water quality, and to adapt the quality standards to consider the ecoregional characteristics of the surface waters of the region.